Determination of prevalence of asymptomatic proteinuria and haematuria in 5-15 year aged school children in southern India - Vadamalai, Rameshkumar (International Journal of Contemporary Pediatrics, 2021)
Background: Chronic renal diseases remain major cause of morbidity and mortality in young children. Although idiopathic nephrotic syndrome takes on chronic course other histopathological variants can lead to rapid progression of disease. Proteinuria in children can be physiological. Hematuria in children is always should be investigated. Persistent proteinuria in children should be investigated for any significant progressive renal disease after excluding orthostatic proteinuria. Although many countries adopt high risk screening in pediatric age group many eastern countries advocate school screening for asymptomatic proteinuria and hematuria using dipstick urine screening. Methods: A 6 month cross sectional study of asymptomatic children aged 5-15 years in metropolitan school for dipstick urine analysis for proteinuria and hematuria. Results: The ratio of male and female children in the study is 1.2:1 (total-1999, male-1056, and female-934). Age group ranged from 5 to 15 with mean 12.13 and standard deviation (SD)-2.46. Maximum number of students in the study are above 10 years of age. Children with isolated asymptomatic proteinuria have significant differences due to their sex (p value-0.005) and hematuria (p value-0.007). Prevalence of asymptomatic proteinuria is 9.8% and hematuria is 1.05%. Prevalence of persistent proteinuria is 1.35%. Conclusions: Prevalence of asymptomatic proteinuria and hematuria can be determined using dipstick urine analysis in school children. Mass screening is cost effective and feasible only if persistent cases of proteinuria are followed up, ruling out orthostatic proteinuria. Although study is feasible, it is cumbersome. High risk screening is the best cost effective method.